2017
DOI: 10.1186/s12948-017-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

How to fit allergen immunotherapy in the elderly

Abstract: Asthma, allergic rhinitis (AR) and atopic dermatitis are very common in young people, but in the latest decades it was increasingly recognized that also individuals of higher ages, including the population over 65 years, are concerned. Actually, it is now acknowledged the aging does not considerably alter the immune response to allergens. Allergen immunotherapy (AIT) is the only treatment that works on the causes of allergy, but elderly people are commonly excluded from AIT, except the cases of insect sting al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Regardless, many physicians are still reluctant to prescribe AIT to elderly patients . This is despite numerous studies having confirmed that the efficacy of AIT in the geriatric population is no different from the non‐geriatric population . Therefore, notwithstanding these limitations, we feel that results from our large‐scale analysis provide insight on trends that may in turn impact any multiple contributors our healthcare system, including physicians, patients, and policymakers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regardless, many physicians are still reluctant to prescribe AIT to elderly patients . This is despite numerous studies having confirmed that the efficacy of AIT in the geriatric population is no different from the non‐geriatric population . Therefore, notwithstanding these limitations, we feel that results from our large‐scale analysis provide insight on trends that may in turn impact any multiple contributors our healthcare system, including physicians, patients, and policymakers.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, of payers that reimburse for healthcare procedures, Medicare remains the largest. Regardless, many physicians are still reluctant to prescribe AIT to elderly patients . This is despite numerous studies having confirmed that the efficacy of AIT in the geriatric population is no different from the non‐geriatric population .…”
Section: Discussionmentioning
confidence: 99%
“…Although epidemiological studies support a decline of the prevalence of allergic diseases in elderly, there are immunological data suggesting that type-2 cytokines pattern is not defective in older age [4547]. Even though debated, late-onset allergy to airborne allergens should be treated with AIT, taking under consideration concomitant diseases that pose contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…Anaphylaxis is a severe and life-threatening hypersensitivity reaction that can affect allergic patients at any age [45]. Clinical manifestations of anaphylaxis caused by food allergens are less frequent in the elderly compared to young subjects [71]. However, although less common, anaphylaxis exhibits a worst prognosis in older patients [72].…”
Section: Clinical Features Of Fas In the Elderlymentioning
confidence: 99%